Edukasi Kesehatan Gigi Dan Mulut Pada Anak Usia Prasekolah Tk Pembina Perumnas Korpri - Nurhayati, Nurhayati; Lussyefrida Yanti; Susilawati; Riska Aisyah Dwi Putri (Gayaku Publisher, 2024)
Counseling aims to describe the factors that influence dental and oral health in pre-school children at the Kindergarten Pembina Perumnas Korpri in Bengkulu. Based on observations, there are still many children at preschool age who do not understand about the health of their teeth and mouth. Even though dental and oral health at their age is important to keep their teeth and mouth healthy until they are old. It's not just the TK Pembina Perumnas Korpri in Bengkulu city that doesn't understand this health issue, even throughout Indonesia there are still many children who don't understand the health of their own teeth and mouth. There have been many cases of tooth decay at school age and their bad breath, which is why education is being held about dental and oral health for preschool age children.